Should Students Engaged to Their Study? (Academic Burnout and School-Engagement among Students) - Arlinkasari, Fitri; Akmal, Sari Zakiah; Rauf, Nur Wahyuni (Universitas Muhammadiyah Metro, 2017)
Inability to deal with lectures efficiently leads students vulnerable to academic burnout. Burnout contributes to the high dropout rate among students, and this phenomenon has occurred on several universities in Indonesia. To overcome these problems, students should generate the feelings, attitudes and positive attitude towards the academic demands, or known as school engagement. School involvement is a predictor of students’ dropout rate. This study aims to analyze the dropout problem in many private universities in Jakarta by examining the psychological variables: academic burnout and school engagement. 208 students from some private university in Jakarta participated and fulfilled two questionnaires: academic burnout and school engagement that has been modified to suit the college setting. Correlation of the variables showed r= - 0.399 (p = 0.000). This means that school engagement plays a role in reducing academic burnout among students. These findings contribute a reference for academic counseling to support the decreasing of students’ dropout rate.